The first selective VAP-1 inhibitor in China, TT-01025-CL: safety, tolerability, pharmacokinetics, and pharmacodynamics of single- and multiple-ascending doses - Yang, Yuanxun; Yu, Lei; Sheng, Zejuan; Lin, Hui; Weng, Zuyi; Song, Wei; Cao, Bei; Zhao, Yu; Gao, Yingsheng; Ni, Shumao; Wang, Huimin; Ma, Tingting; et al. (Frontiers in Pharmacology, 2024)
Introduction: TT-01025-CL is an oral, irreversible small molecule that potently inhibits vascular adhesion protein-1 (VAP-1) for the treatment of inflammation associated with non-alcoholic steatohepatitis (NASH). The objectives of this study were to evaluate the safety/tolerability, pharmacokinetics, and pharmacodynamics of TT-01025-CL, a vascular adhesion protein-1 (VAP-1) inhibitor, in Chinese healthy volunteers.Methods: Double-blind, placebo-controlled, dose-escalation studies were conducted in subjects randomized to receive oral once-daily TT-01025-CL (ranges:10-300 mg [single dose]; 20-100 mg for 7 days [multiple doses]) or placebo under fasting conditions. Safety and tolerability were monitored throughout the study. Pharmacokinetic parameters were determined by non-compartment analysis.The activity of SSAO-specific amine oxidase and the accumulation of methylamine in plasma were evaluated as pharmacodynamic biomarkers.Results: A total of 36 (single dose group) and 24 (multiple dose group) subjects were enrolled in the study. No serious AEs were reported, and no subject discontinued due to an AE. All TEAEs were mild and moderate in intensity. No dose-dependent increase in intensity or frequency of events was observed. TT-01025-CL was rapidly absorbed after administration. In the SAD study, median Tmax ranged from 0.5-2 h, and mean t1/2z ranged from 2.09-4.39 h. PK was linear in the range of 100-300 mg. The mean Emax of methylamine ranged from 19.167-124.970 ng/mL,with mean TEmax ranging from 13.5-28.0 h. Complete inhibition (>90%) of SSAO activity was observed at 0.25-0.5 h postdose and was maintained 48-168 h post-dose. In the MAD study, steady state was reached by day 5 in the 40 mg and 100 mg dose groups. with mean Emax ranging from 124.142-156.070 ng/mL and mean TEmax ranging from 14.2-22.0 h on day 7. SSAO activity in plasma was persistently inhibited throughout the treatment period.No evident change of methylamine and SSAO activity was observed in the placebo groups.Conclusion: TT-01025-CL was safe and well-tolerated at a single dose of up to 300 mg and multiple doses of up to 100 mg once daily for 7 consecutive days. The absorption and elimination occurred rapidly in healthy volunteers. Linearity in plasma exposure was observed. TT-01025-CL inhibited SSAO activity rapidly and persistently i. The profile of TT-01025-CL demonstrates its suitability for further clinical development.